Evaluating the Effectiveness of Adult Day Care on Alleviating Caregiver Stress/Burden - Lessep Duncan; Joan Bowla; Rosena Tanis (University of North Florida, 2016)
Though not extensive, the literature points to the efficacy of Adult Day Care (ADC) in alleviating stress on caregivers in several and differing ways. In line with this evidence, the findings from the evaluation of Northwest Focal Point's (NWFP) ADC program conducted by the Florida Atlantic University Evaluation Team indicates that ADC provides necessary relief and reduces the strain of caregiving on caregivers. Two measurement instruments: one to measure the level of caregiver strain and one to measure the effectiveness of ADC in alleviating this strain comprising five dimensions of caregiving strain and five dimensions of ADC impact in reducing strain were used to evaluate NWFP ADC program effectiveness. Whereas findings indicated that the ADC reduced caregiving strain in most dimensions, the evaluation pointed to the greatest impact of ADC was in increasing caregivers' confidence to provide care. Another significant impact identified in the evaluation related to the ADC reducing the caregivers' loved one dependence on the caregiver.